An algorithm combining sedimentation experiments for pipe erosion investigation - Yao, Liming (2023)
Hydraulic fracturing is an essential technology for continuously developing non-renewable energy, such as oil and gas. The erosion of solid-liquid two-phase flow in hydraulic fracturing is a theoretical problem that needs to be solved urgently. In the current computational fluid dynamics-discrete element method (CFD-DEM) research, we present calculation methods for the collision restitution coefficients of quartz particle in Newtonian fluids (1 mPa⋅s) and non-Newtonian fluids (10 mPa⋅s and 20 mPa⋅s). The influence of power-law fluid is considered in the algorithm, and the problem of particle penetration in the CFD-DEM method is optimized. These experimentally obtained collision restitution coefficients are incorporated into the optimized CFD-DEM method to consider the influence of fluid viscous forces on particle collisions. The accuracy of the numerical simulation method in this paper is verified by particle settlement and erosion experiments. The elbow erosion experiment is then used to validate the correctness of the erosion simulation. Finally, the erosion behavior of the fracturing pipe (elbow and tee junction) under different conditions is analyzed.